Integrating Islamic Values into Digital Learning: A Solution for Character-Based Education in the Technological Era - Yususf Yusuf; Wati Karmil; Novianti Muspiroh; Moh. Alfi Sena Nur Fajri (UIN Siber Syekh Nurjati Cirebon, 2026)
Amid the vibrant surge of digital transformation in education, an academic unease arises: how can Islamic values endure and flourish within a fast-paced, algorithm-driven digital space? This study delivers a critical warning—those digital platforms, once considered neutral, are now shaping the reasoning and ethics of younger generations without a clear spiritual foundation. Within the global discourse on character education, numerous studies have revealed the failure of online learning in cultivating students’ moral depth—even in religious environments. This research aims to address that gap by offering a new approach: exploring the contextual, participatory, and reflective integration of Islamic values into digital learning through a multi-site study of three State Islamic High Schools in Cirebon Regency. Using a qualitative instrumental case study design, data were gathered via interviews, online observations, digital content documentation, and triangulation from 36 key informants. Findings indicate that when Islamic values are not merely taught, but visually, symbolically, and productively embedded in digital spaces, students do not simply absorb the values—they become producers of those values. Models such as Ngaji Digital Bareng (Collective Digital Quran Study), contemplative posters, and student-created da'wah videos serve as tangible evidence of character transformation. This study demonstrates that technology, when approached with spiritual awareness, is not a threat to Islamic values, but rather a new arena for civilizational development. The study recommends reconstructing digital madrasah curricula based on value-driven frameworks and enhancing cross-disciplinary teacher training in digital spiritual pedagogy.